The Feature of Project-Based Learning and Differentiated Instruction Practices in Biology Learning - Suci Fajrina; Ria Anggriyani; Fitri Arsih; Muhyiatul Fadilah; Helendra; Zulyusri; Eby Restudila; Asya Kharisma; Ayu Melisa Putri (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to examine Biology teachers' views on the effectiveness of Project Based Learning (PjBL) in building a conducive learning environment that increases student involvement and socio-cultural awareness in Biology learning in Indonesia. In addition, this research aims to explore the methods used by Biology teachers in implementing differentiation in Biology education in the Indonesian context. The approach was taken with a sequential mixed methods strategy, which ensured comprehensive data collection. and the use of qualitative and quantitative methods starting with distributing questionnaires to 200 Biology teachers, followed by focus group interviews with eight volunteer educators. The results of the study state that Biology educators consider project-based learning as a useful teaching method that contributes to increased student engagement, increased social dynamics in the classroom, cultural appreciation, and effective implementation of strategies for differentiated learning. These findings have implications across multiple domains, including teacher professional development, academic administration, curriculum design, and decision-making processes. Furthermore, the insights gained from this research may extend beyond the boundaries of Biology education, attracting interest from stakeholders in a variety of academic disciplines.